MENTORING THE MANUFACTURE OF ECO-FRIENDLY DISPOSABLE PLATES FROM ARECA NUT FRONDS BY PT PUPUK ISKANDAR MUDA IN GAMPONG BLANG ME, BIREUEN - Emmia Tambarta Kembaren; Fadli; Ade Firmansyah Tanjung; Rezki Zufina; Milna (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2023)
PT Pupuk Iskandar Muda (PIM) is committed to developing and empowering the community through Corporate Social Responsibility (CSR) activities with the social responsibility to maintain the sustainability of the company by implementing environmentally sound activities within the economic, social, religious and cultural environment around the company. One of the community environments promoted by PT PIM is the Paya Nie area in Gampong Blang Me, North Aceh Regency, Aceh Province. In 2023, a program recommendation was made to innovate areca fronds into eco-friendly disposable plates. The program's support for the production of eco-friendly disposable plates from areca fronds in Paya Nie Gampong Blang Me, North Aceh, is seen as an environmentally friendly innovation in the North Aceh area. This is because the use of areca nut plant waste has never been done before in North Aceh. The impact of the program implementation is divided into 3 (three) categories, namely: (1) the impact of the program on the change in knowledge of the program participants has achieved the target of 100% (> 50%); (2) the impact on the change in behaviour of the program participants has achieved the target of 75% (> 50%); (3) in general, 60% of the program participants experienced an increase in income of more than 40%; (4) the business asset used is a disposable plate press, which is used to the maximum (100%) during the program.